(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2019)
Solar arrays are nonlinear devices, and as a result the output current-voltage are dependent on their bias point. Power can be optimized by biasing the PV cell’s voltage at the maximum power point (MPP). The PV array is affected by solar irradiation, cell temperature, age, loading condition, and other conditions. These variations are also having nonlinear responses, which need to control with the help of buck boost converter to ensure that maximum power output is transferred to the load. This paper summarizes some of important applications of the MPPT. A comparison between direct and indirect connected to resistive load with MPPT in terms of PV total energy. The MPPT algorithm, which is based on the perturb and observe method) plays an important function that is developed in MATLAB Simulation, and the outputs are observed. It includes module BP SX 150S for a solar photovoltaic. This module approximately provides a maximum power of 150 W.